Pertimbangan Hakim Dalam Upaya Pemenuhan Hak Korban KDRT Pada Undang-Undang Nomor 23 Tahun 2004 - Jhoni Lie; R. Rahaditya (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Fundamentally, it is the right of every individual to be able to form a family and continue their offspring, as this is regulated in Article 28B of the 1945 Constitution of the Republic of Indonesia as the basic constitutional foundation of the state. However, in reality, the idea of balance in a harmonious family is often undermined by the occurrence of domestic violence, especially against women. The act of domestic violence is an act committed by affecting a person's right to freedom in accordance with the law within the scope of the household, one of which occurred in Decision of the West Jakarta District Court number 420/Pid.Sus/2023/Pn Jkt.Brt. In analyzing this issue further, the author uses a normative juridical research method with a statutory approach and a case approach obtained through a literature study using third-party data sources such as journals, papers, published articles and other literature sources. The data that has been obtained is processed and compiled with a descriptive method to be able to describe in detail the condition of the problems to be discussed in the writing, so that a concrete solution can be found from the existing discussion. The end of this discussion is, in enforcing the law against the occurrence of domestic violence must also be able to focus more on considering the fulfillment of victims' rights.